Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
Spire Pitou, The players' return to Versailles, 1723-1757 Charlotte Hogsett, Jean Baptiste Dubos on art as illusion Clifton Cherpack, Jacques le fataliste and le Compère Mathieu William H. Trapnell, The 'philosophical' implications of Marivaux's Dispute Barry Ivker, Towards a definition of libertinism in 18th-century French fiction Mark Poster, The concepts of sexual identity and the life cycle in Restif's utopian thought